Corpus Linguistics Research: Analyse the Use of Article in Novel “The Body in The Library” by Agatha Christie - Dwi Nur Azizah Fitriani; Lilia Indriani (Journal of Research on Applied Linguistics, Language, and Language Teaching, 2021)
The study aims to analyse the article in "The Body in The Library" written by Agatha Christie. "The Body in The Library" is a fiction crime about an old amateur detective, Miss Marple, even though she just an old ordinary single woman who lives alone in a rural area but have a great instinct to solve the mystery. An article used to define a definite or an indefinite noun also a countable and uncountable noun. It used to know references of the noun before in the story in a novel. The method used in this research is a descriptive qualitative method that includes the stages of data collection, analysing the data and then making a conclusion about it. The analysis "The Body in The Library" written by Agatha Christie used article the, a and an. The article function in "The Body in The Library" novel by Agatha Christie refers to define and indefinite noun.